Anemia in the elderly: not always what it seems. - Marco Cerrano; Elena Crisà; Valentina Giai; Mario Boccadoro; Dario Ferrero (Mediterranean Journal of Hematology and Infectious Diseases)
Anemia in the elderly is a common but challenging clinical scenario. Here we the described the case of an elderly women who presented with anemia and elevated inflammation markers. After a complete diagnostic workup a clear etiology of the anemia could not be found and eventually a bone marrow biopsy was performed: she was diagnosed with myelodysplastic syndrome. She responded well to erythropoietin treatment but her inflammation markers remained elevated and a positron emission tomography was eventually performed. It turned out that the patient suffered from giant cell artheritis, and after steroid treatment her anemia completely resolved. Our case outlines that it is necessary to pay particular attention to anemia of chronic inflammation, which could be due to several and often masked conditions. Myelodysplatic syndromes should be considered when other causes have been ruled out, but their diagnosis can be difficult and requires expertise in the field.